2022
DOI: 10.56717/jpp.2022.v01i02.010
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal, antiradical, anti-inflammatory and antineoplastic activities of essential oils of some medicinal plants of the Annonaceae family of Chad and Cameroon

Abstract: Yeasts infections, cancer and other diseases associated with free radical generation and inflammation are currently a critical public health issue that needs innovative control measures. In order to search for solutions, this study was designed to assess the antifungal, radical scavenging, anti-inflammatory, and antineoplastic activities of essential oils from four Annonaceae plants (Monodora myristica, Xylopia aethiopica, and Xylopia parviflora) collected in Chad and Cameroon. Essential oils were extracted by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…On the other hand, this chemotype combining 1,8-cineole and β -pinene has been reported by several authors from different origins (Cameroon [ 39 ], Nigeria [ 13 ], and Congo Brazzaville [ 56 ]). β -Pinene has been described as the primary compound in several chemotypes [ 14 , 19 , 25 , 31 , 34 36 ]. Finally, trans-pinocarveol [ 27 , 35 ], myrtenol [ 27 ], α -pinene [ 19 , 36 , 44 ], and terpinen-4-ol [ 7 , 37 ] have been reported in a certain number of studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, this chemotype combining 1,8-cineole and β -pinene has been reported by several authors from different origins (Cameroon [ 39 ], Nigeria [ 13 ], and Congo Brazzaville [ 56 ]). β -Pinene has been described as the primary compound in several chemotypes [ 14 , 19 , 25 , 31 , 34 36 ]. Finally, trans-pinocarveol [ 27 , 35 ], myrtenol [ 27 ], α -pinene [ 19 , 36 , 44 ], and terpinen-4-ol [ 7 , 37 ] have been reported in a certain number of studies.…”
Section: Resultsmentioning
confidence: 99%
“…It is widely used in traditional medicine in the treatment of cough, dysentery, edema, rheumatism stomachache, dizziness, amenorrhea, lumbago, and neuralgia [10][11][12][13]. Some studies have also demonstrated the efcacy of X. aethiopica oil as anticancer [14][15][16], antioxidant [7,12,[17][18][19][20], antimicrobial [13,19,[21][22][23][24][25][26][27][28][29][30], anti-infammatory [18,22,31], anticholinesterase [7], antimalarial [13], antitrypanosomal [13], antidepressant [32], and insecticidal [33]. Te chemical composition of the essential oil of X. aethiopica fruits is very diverse.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation